STATUS OF WOMEN TO GENDER INEQUALITY - Pradhan, Tanushree (International Journal of Psychosocial Rehabilitation, 2020)
The status of Women is how the society perceives a woman and not what it should be. Gender equality includes protection from sexual harassment and right to work with dignity, which is a universally recognized basic human right. Empowerment of women is highly accelerated by the closing gender gap in education. Women represent half of the world’ s population, and gender inequality exists in every nation on the planet. Denying women and girls equality and fairness not only hurts them, but also hinders the rest of the society. Unless societies, governments and non – governmental organisations around the world come together and make a concentrated effort to empower and grant equality to women. Until and unless, women’ s economic security is strengthened, one will not be able to eliminate poverty, achieve gender equality, or realize any genuine progress.